1984
DOI: 10.1007/bf00007667
|View full text |Cite
|
Sign up to set email alerts
|

The chironomid fauna of four shallow, humic lakes and their representation by subfossil assemblages in the surficial sediments

Abstract: A comparison of the present chironomid fauna of four shallow, humic lakes with the subfossils of surficial sediments is made . The chemistry and benthos of the lakes investigated varied greatly . Results indicate a reasonable correlation between biocenoses and thanatocenoses, but a marked under-representation of Procladius is apparent . It is suggested that, at least in shallow, humic lakes, Procladius be excluded in attempts to reconstruct chironomid communities from subfossils .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…Descriptive salinity classification is modified after that of Gasse et al (1987): freshwater: Ͻ500 S cm Ϫ1 , oligosaline: 500-5,000 S cm Ϫ1 , mesosaline: 5,000-20,000 S cm Ϫ1 , polysaline: 20,000-40,000 S cm Ϫ1 , and metasaline: Ͼ40,000 S cm Ϫ1 . Fossil invertebrates were analyzed in 34 contiguous 1-cm increments of core NS91.1-S. Subsamples (2.0-10.0 ml) were prepared by dispersing the sediment matrix in warm 10% potassium hydroxide (Walker and Paterson 1985) and rinsing through 250-m and 105-m mesh sieves. The retained residues were scanned at ϫ25 under a Wild M10 dissecting microscope, and remains of planktonic cladocerans, benthic cladocerans, chironomids, and other aquatic arthropods were identified at ϫ40-100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive salinity classification is modified after that of Gasse et al (1987): freshwater: Ͻ500 S cm Ϫ1 , oligosaline: 500-5,000 S cm Ϫ1 , mesosaline: 5,000-20,000 S cm Ϫ1 , polysaline: 20,000-40,000 S cm Ϫ1 , and metasaline: Ͼ40,000 S cm Ϫ1 . Fossil invertebrates were analyzed in 34 contiguous 1-cm increments of core NS91.1-S. Subsamples (2.0-10.0 ml) were prepared by dispersing the sediment matrix in warm 10% potassium hydroxide (Walker and Paterson 1985) and rinsing through 250-m and 105-m mesh sieves. The retained residues were scanned at ϫ25 under a Wild M10 dissecting microscope, and remains of planktonic cladocerans, benthic cladocerans, chironomids, and other aquatic arthropods were identified at ϫ40-100.…”
Section: Methodsmentioning
confidence: 99%
“…The samples yielded an average of 104 (31-192) chironomid fossils; cladoceran fossils (0-257 per sample) were concentrated in a few horizons at 4-10 cm depth. The invertebrate data are presented as fossil accumulation rates (fossils cm Ϫ2 yr Ϫ1 ), based on studies suggesting that their preservation in sediments of this age is complete and taxon independent (Walker et al 1984;Frey 1988). Statistical treatment was limited to the eight most common chironomid species, which together comprise an average of 97% (81-100%) of the fossil chironomid sum.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Walker et al (1984) suggested that Procladius may be poorly preserved in some lake sediments. However, in our study, remains of Procladius are common in both living and subfossil assemblages (Fig.…”
Section: Occurrence Of Taxa In Lake De Waaymentioning
confidence: 99%
“…It is unlikely, however, that transport of remains can cause a complete integration of littoral and profundal communities (Frey 1988;. Moreover, transport of remains does not play an important role in all lakes Walker et al 1984;. The most detailed study previously available that compared living and subfossil assemblages of chironomids by demonstrated that communities and their remains were qualitatively and quantitatively similar in a number of lakes.…”
Section: Taphonomy Of Invertebrate Remainsmentioning
confidence: 99%
See 1 more Smart Citation